The equation of the graph in standard form is 2x + 3y = -6
The attached figure represents the missing piece in the question
The graph passes through the points
(-3,0) and (0,-2)
The linear equation is then calculated using:
[tex]y = \frac{y_2 -y_1}{x_2 -x_1} * (x-x_1) + y_1[/tex]
So, we have:
[tex]y = \frac{-2 -0}{0+3} * (x-0) -2[/tex]
Evaluate the expression
[tex]y =-\frac 23x - 2[/tex]
Multiply through by 3
3y = -2x - 6
Add 2x to both sides
2x + 3y = -6
Hence, the equation in standard form is 2x + 3y = -6
Read more about linear equations at:
https://brainly.com/question/14323743
#SPJ1